2019
DOI: 10.1093/eurheartj/ehz332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of intracoronary imaging. Part 2: acute coronary syndromes, ambiguous coronary angiography findings, and guiding interventional decision-making: an expert consensus document of the European Association of Percutaneous Cardiovascular Interventions

Abstract: This consensus document is the second of two reports summarizing the views of an expert panel organized by the European Association of Percutaneous Cardiovascular Interventions (EAPCI) on the clinical use of intracoronary imaging including intravascular ultrasound (IVUS), optical coherence tomography (OCT), and near infrared spectroscopy (NIRS)-IVUS. Beyond guidance of stent selection and optimization of deployment, invasive imaging facilitates angiographic interpretation and may guide treatment in acute coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
164
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 231 publications
(186 citation statements)
references
References 107 publications
2
164
0
6
Order By: Relevance
“…Median follow-up days of ACS non-culprit lesions were 10 days. [6][7][8][9][10][11][12][13] A representative case is shown in Figure 1. All lesions were divided into FFR and QFR tertiles, as previous studies.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Median follow-up days of ACS non-culprit lesions were 10 days. [6][7][8][9][10][11][12][13] A representative case is shown in Figure 1. All lesions were divided into FFR and QFR tertiles, as previous studies.…”
Section: Study Populationmentioning
confidence: 99%
“…6 Optical coherence tomography (OCT) can detect high-risk anatomical plaque features that have been established as pathogenically fundamental in acute coronary syndrome (ACS) and sudden cardiac death. [7][8][9] Our group recently reported that the development of OCTdefined thin-cap fibroatheroma (TCFA) was associated with physiological severity as represented by the FFR in intermediate-to-severe stenoses. 10 A recent study also showed that not only the FFR but also microvascular dysfunction as represented by the IMR is an independent predictor of the presence of OCT-defined TCFA.…”
Section: Introductionmentioning
confidence: 99%
“…Near-infrared spectroscopy-intravascular ultrasound (IVUS) may help to quantify the lipid content of the coronary plaque and could potentially be an important tool to predict future events. Besides, this imaging modality could possibly distinguish whether the MINOCA event is caused by a vulnerable plaque that has ruptured or whether CAD is absent [21]. However, data on intravascular imaging in MINOCA patients is still sparse.…”
Section: Plaque Disruption and Plaque Erosionmentioning
confidence: 99%
“…However, in these studies the positive predictive value of the studied invasive imaging modalities in predicting MACE was low. Therefore their routine use to stratify risk in the clinical setting is currently not recommended [17]. Combination of plaque morphology and physiology, particularly estimation of the ESS using computational fluid dynamic analysis of intravascular imaging data seems to provide additional prognostic information and detection of vulnerable plaques with a positive predictive value that exceeds > 50% [11,18].…”
Section: Discussionmentioning
confidence: 99%